P04 - Obstetric and neonatal outcomes in gestational diabetes: the influence of maternal body mass index and gestational weight gain (Journal of Statistics on Health Decision, 2019)
Introduction: Due to the growing prevalence of obesity, more women are overweight in early pregnancy (1). Previous studies demonstrated that pre-obesity/obesity is associated with adverse neonatal and obstetric outcomes, namely pre-eclampsia, cesarean delivery, prematurity, macrosomia, neonatal intensive care unit admissions and stillbirth (2,3). There is also evidence that excessive gestational weight gain is associated with an increased risk of gestational hypertension, gestational diabetes (and, inclusively, pharmacological therapy), delivery by cesarean section, postpartum weight retention, macrosomia and neonatal intensive care unit admissions (4,5). Some studies also shown that obese women tend to have an earlier gestational diabetes, more insulin resistance with increased risk of type 2 diabetes, which might lead to a poorer long-term prognosis (6).Objective: To evaluate the influence of maternal pre-pregnancy body mass index and gestational weight gain on blood glucose levels at diagnosis of gestational diabetes, obstetric and neonatal outcomes.Methods: Retrospective observational study including women with gestational diabetes and follow-up at Baixo Vouga Hospital Center between January 2015 and June 2018. Multiple gestation pregnancies, cases of loss of follow-up and stillbirths were excluded. Pregnant women were divided in 4 categories according to pre-pregnancy body mass index: low weight (
Keywords: Gestational Diabetes; Maternal Body Mass Index; Gestational Weight Gain